Social Capital and the Family: Evidence that Strong Family Ties Cultivate Civic Virtues - Martin Ljunge (Research Institute of Industrial Economics (IFN), 2013)
I establish a positive relationship between family ties and civic virtues, as captured by disapproval of tax and benefit cheating, corruption, and a range of other dimensions of exploiting others for personal gain. I find that family ties are a complement to social capital, using within country evidence from 83 nations and data on second generation immigrants in 29 countries with ancestry in 85 nations. Strong families cultivate universalist values and produce more civic and altruistic individuals. The results provide a constructive role for families in promoting family values, which challenge an amoral familism. Moreover, strong families are complementary with more developed and democratic institutions. The results provide a constructive role for families in promoting family values that support successful societies with a high state and fiscal capacity.
Keywords: A13; H26; P16; Z13; 330; Family ties; Civic; Family values; Cultural transmission; Altruism; Social capital